SMALLHOLDERS AT THE CROSSROADS: BARRIERS TO EUDR COMPLIANCE AND EQUITY IN PALM OIL SUPPLY CHAINS - Judijanto, Loso (Seven Editora, 2025)
The European Union Deforestation Regulation (EUDR) introduces a new layer of environmental accountability in global commodity markets, with major implications for smallholder farmers in palm oil-producing countries. Despite their crucial role in the palm oil sector, smallholders remain structurally disadvantaged in complying with EUDR standards due to complex regulatory, technical, and socioeconomic barriers. This study aims to critically explore the multifaceted obstacles faced by smallholders in achieving EUDR compliance while assessing the equity risks embedded in current supply chain frameworks. A qualitative literature review method was employed, drawing on 80 peer-reviewed articles, policy briefs, and technical reports published between 2015 and 2025. Data were collected using purposive sampling of scholarly sources from Scopus, ScienceDirect, JSTOR, and policy think tanks, focusing on regions such as Indonesia, Malaysia, and Thailand. Thematic analysis was used to extract recurring patterns, bottlenecks, and structural inequities. The results reveal that only 24–38% of smallholders possess the technical and legal infrastructure to meet EUDR traceability and documentation requirements. Institutional limitations, including low access to finance, weak land tenure security, and poor digital infrastructure, further marginalize their position. Compliance costs consume up to 40% of smallholder incomes, threatening widespread exclusion. The study concludes that unless proactive, equity-oriented reforms are implemented, EUDR risks entrenching a dual-tier system that favors large-scale producers. Future research should explore scalable, low-cost compliance technologies and policy innovations that center justice and inclusivity for smallholders.DOI: https://doi.org/10.56238/sevened2025.029-009